建築設計之著作權研究 Study of Copyright for Architectural Design - 蘇南 Nan Su; 方星淵 Hsing-Yuan Fang (Kējì Fǎxué Pínglùn, 2013)
建築著作相較其他著作於我國立法甚晚，相較其他著作，如電腦軟體、商品、工業產品、影音、動漫等有著繁複的階段，因為建築著作的圖面完成，即為建築著作，但其後尚有依照圖面所製之建築模型與建築物，並且過程迭有更動，更牽涉建築法規，其原創性之認定困難，問題眾多。就起始階段而言，著作權歸屬即可能有問題，創作參與者可能有執業建築師、聘僱之建築師及建築設計師等，更有可能是國外建築師設計，國內建築師作安全考核，過往有學者提出以負擔安全責任因素，故認著作權應歸屬執業建築師，如此是否合乎著作權法之精神，非無疑義。另建築物因已有民法上出租規 定，然模型與建築圖說是否無出租權之可能，此雖我國現行無相關研究，惟實務不乏特殊用途建築圖說出租情況，本文認應予探討。另建築著作體系龐大，諸如草圖、規劃圖、設計圖、結構、水電、施工說明、透視、建築模型、建築物、室內設計等圖說，究竟保護範圍若何；按建築師觀點應全然納入，惟此不無影響他人依建築規範設計而致侵權之衝突。是諸多建築著作爭議，應予比較國內外法律及實務並深入研究，以利我國就建築著作有更為細緻之立法。 Architectural works in our legislation are very late compared to other works, such as computer program, commodities, industrial products, audio, video, animation, and so have a complex phase. The final outcomes of building design are called architectural works, but then buildings are constructed in accordance with drawings and models of buildings. Because architectural works must be according to Building Codes, then the originality of architectural works is difficult to identify. On the initial stage, the copyright ownership may be a problem: architectural works may be created by the teams of the practicing architect, hired architects and building designers, and it’s possible to be combine foreign architects with design and domestic structure engineers of safety. Some scholars advocated that copyright vested in the practicing architect due to the liability of safety, whether it complies with the legislative intent of Copyright Act. Although the rental of buildings is pro-vided in the Civil Code, these studies lack building models and architectural works to rental rights, but it is a common practice in construction. This article will discuss the above-mentioned issues. However, building constructions depend on architecture drawings and models, then the architecture drawings include sketches, paint regulation, design drawings, structural drawings, water and electricity drawings, working drawing, perspective drawings, architectural model, interior design and other drawings－which belong to the objectives of copying right? In architects’ view, these should be completely incorporated, but it may be conflicting because architecture design must be based on Building Codes. This article will investigate these issues from domestic and international perspectives in order to facilitate the more nuanced legislation for copyright of architectural works.